Mutations in TRAPPC11 are associated with a congenital disorder of glycosylation. Issue 2 (26th November 2016) - Matalonga, Leslie; Bravo, Miren; Serra‐Peinado, Carla; García‐Pelegrí, Elisabeth; Ugarteburu, Olatz; Vidal, Silvia; Llambrich, Maria; Quintana, Ester; Fuster‐Jorge, Pedro; Gonzalez‐Bravo, Maria Nieves; Beltran, Sergi; Dopazo, Joaquin; et al.
Abstract : We report the first description of a patient with defects in both N‐ and O‐glycosylation combined with a delayed vesicular transport in the Golgi apparatus (GA) due to mutations in TRAPPC11, a subunit of the TRAPPIII complex. TRAPPIII is implicated in the anterograde transport from the endoplasmic reticulum (ER) to the ER‐Golgi intermediate compartment as well as in the vesicle export from the GA. This report expands the spectrum of genetic alterations associated with congenital disorders of glycosylation. ABSTRACT: Congenital disorders of glycosylation (CDG) are a heterogeneous and rapidly growing group of diseases caused by abnormal glycosylation of proteins and/or lipids. Mutations in genes involved in the homeostasis of the endoplasmic reticulum (ER), the Golgi apparatus (GA), and the vesicular trafficking from the ER to the ER–Golgi intermediate compartment (ERGIC) have been found to be associated with CDG. Here, we report a patient with defects in both N‐ and O‐glycosylation combined with a delayed vesicular transport in the GA due to mutations in TRAPPC11, a subunit of the TRAPPIII complex. TRAPPIII is implicated in the anterograde transport from the ER to the ERGIC as well as in the vesicle export from the GA. This report expands the spectrum of genetic alterations associated with CDG, providing new insights for the diagnosis and the understanding of the physiopathological mechanisms underlying glycosylation disorders.